2012
DOI: 10.1021/jm201371y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Quantitative Structure–Activity Relationship (Cell-QSAR): Conceptual Dissection of Receptor Binding and Intracellular Disposition in Antifilarial Activities of Selwood Antimycins

Abstract: We present the cellular quantitative structure–activity relationship (cell-QSAR) concept that adapts ligand-based and receptor-based 3D-QSAR methods for use with cell-level activities. The unknown intracellular drug disposition is accounted for by the disposition function (DF), a model-based, nonlinear function of a drug’s lipophilicity, acidity, and other properties. We conceptually combined the DF with our multispecies, multimode version of the frequently used ligand-based comparative molecular field analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Some cell organelles contain aqueous phases with the pH values differing from that of cytoplasm: lysosomes are at the low end with pH ~ 5 and the interior of mitochondria is at the opposite end of the range with pH ~ 8. Therefore, dissolved weak bases prefer lysosomes [36,37] and dissolved weak acids accumulate in mitochondria [48]. For instance, the cells of liver and kidney have a higher concentration of lysosomes [34,39] and mitochondria [40] than those of heart and muscle, and uneven accumulation of ionizable compounds in these organs can be explained by the solvation of ionized species.…”
Section: Other Claims Meant To Support the Transporters-only Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Some cell organelles contain aqueous phases with the pH values differing from that of cytoplasm: lysosomes are at the low end with pH ~ 5 and the interior of mitochondria is at the opposite end of the range with pH ~ 8. Therefore, dissolved weak bases prefer lysosomes [36,37] and dissolved weak acids accumulate in mitochondria [48]. For instance, the cells of liver and kidney have a higher concentration of lysosomes [34,39] and mitochondria [40] than those of heart and muscle, and uneven accumulation of ionizable compounds in these organs can be explained by the solvation of ionized species.…”
Section: Other Claims Meant To Support the Transporters-only Hypothesismentioning
confidence: 99%
“…We have shown that in several cases of drug action in cell suspension, the kinetics of membrane transport does not need to be considered and a pseudo-equilibrium accumulation is sufficient to create good-quality, model-based QSARs for a limited series of compounds [47,48]. The agreement of the model with experimental data indicates that drugs were distributed according to the lipophilic-hydrophilic equilibrium, which eliminates the involvement of transporters.…”
Section: Other Claims Meant To Support the Transporters-only Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, f i and f j are independent variables in the correlation equations, which are calculated before optimization assuming that the pH value of the medium is known. For cell-QSAR applications predicting binding affinities of the receptors inside the cells, the pH of the medium may differ from the plasma value and can become an optimized parameter for some simple speciation cases [78]. …”
Section: Introductionmentioning
confidence: 99%
“…In terms of the equation, log K is an MSMM-CoMFA expression for the receptor binding and the remaining terms (log DF) describe disposition function. Cell-based QSAR was successfully used to study the antifilarial activities of antimycin analogues 61 . Compared to the models of traditional CoMFA method, DF was a necessary part to ensure reliably predictive abilities.…”
mentioning
confidence: 99%